The Glasgow Prognostic Score and fibrinogen to albumin ratio as prognostic factors in hospitalized patients with COVID-19 - Kuluozturk, Mutlu; Deveci, Figen; Turgut, Teyfik; oner, Onsel (Taylor & Francis Ltd, 2021)
Aim: This study aims to determine the prognostic value of the Glasgow Prognostic Score (GPS) and fibrinogen to albumin ratio (FAR) in patients with COVID-19. Methods: Electronic database records of 400 patients with COVID-19 were retrospectively analyzed and the initial levels of CRP, albumin, fibrinogen values were recorded. The ground-glass opacities (GGO) and consolidations were evaluated on thorax CT. Hospital mortality and the need for intensive care unit (ICU) transfer were determined as adverse outcomes. Results: It was determined that 345 patients (86.25%) were discharged while 31 patients (7.75%) were transferred to ICU in addition to 24 patients who died (6%). The rates of deaths and transfers to ICU were significantly increased in GPS 2 group compared to both GPS 0 and 1 groups. Additionally, increased FAR was observed in patients who died and transferred to ICU compared to the discharged patients. The FAR was significantly increased in patients with diffuse GGO. Logistic regression analysis indicated that FAR >= 144.59 and the presence of GPS 2 were independent predictors of the adverse outcomes in COVID-19 patients. Conclusion: Our results demonstrated that the GPS and FAR could possess a predictive value for adverse outcomes in patients with COVID-19.
Keywords: COVID-19; GPS; FAR; mortality; need for intensive care unit